2014
DOI: 10.1038/jid.2013.334
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes Induces an IL-17 Response in Acne Vulgaris that Is Regulated by Vitamin A and Vitamin D

Abstract: Acne vulgaris is the most common skin disorder affecting millions of people worldwide and inflammation resulting from the immune response targeting Propionibacterium acnes plays a significant role in its pathogenesis. In this study, we have demonstrated that P. acnes is a potent inducer of Th17 and Th1, but not Th2 responses in human PBMCs. P. acnes stimulated expression of key Th17-related genes, including IL-17A, RORα, RORc, IL-17RA and IL-17RC, and triggered IL-17 secretion from CD4+, but not CD8+ T cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
199
4
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(237 citation statements)
references
References 43 publications
23
199
4
11
Order By: Relevance
“…Recent reports suggest that T-helper type 17 (Th17) and Th1 lymphocytes are involved in the pathogenesis of acne (1)(2)(3). Systemic isotretinoin remains the most efficient treatment for acne, but its complete mechanism of action is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggest that T-helper type 17 (Th17) and Th1 lymphocytes are involved in the pathogenesis of acne (1)(2)(3). Systemic isotretinoin remains the most efficient treatment for acne, but its complete mechanism of action is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Inflammation resulting from the immune response targeting Propionibacteriumacnes(P. acnes)has a significant role in acne pathogenesis. In a recent study, it has been demonstrated that P. acnes is a potent inducer ofTh17, and that 1,25OH2D inhibits P. acnes-induced Th17 differentiation, and thereby could be considered as an effective tool in modulating acne ,that demonstrate the important role of vitamin D in skin infections [27] . Results of [28] showed that Gram negative bacteria were more resistant to vitamin E effect than Gram positive bacteria, this resistance towards antibacterial substance may be related to lipopolysaccharides (LPS) in their outer membrane.…”
Section: Then Psaeruginosa(5)mentioning
confidence: 99%
“…Interleukin-17A atau yang sering disebut pula sebagai IL-17 8 merupakan sitokin proinflamasi yang poten, 9 diproduksi oleh sel T helper (Th)17 yaitu merupakan subset dari sel T CD4 + . 8 IL-17, berperan penting dalam pembentukan penyakit inflamasi, 10 yaitu antara lain psoriasis, artritis reumatoid, penyakit Crohn, penyakit obstruksi saluran napas, sklerosis sistemik, 9 penyakit kulit infeksi seperti Staphylococcus, 11 serta penyakit kulit inflamasi seperti dermatitis kontak alergi dan atopik. Pada AV, sekresi IL-17 dari sel Th17 didapatkan melalui diferensiasi sel T CD4 + dengan bantuan ketiga sitokin yang diinduksi oleh P. acnes, yaitu IL-1β, IL-6, dan TGF-β.…”
Section: Pendahuluanunclassified
“…11 Pada serum pasien AV dengan lesi inflamasi didapatkan peningkatan kadar IL-17, TNF-α, IL-4, dan interferon (IFN)-γ dibanding dengan orang normal. 12 Penelitian ini bertujuan membandingkan apakah ada perbedaan kadar IL-17 di dalam serum antara pasien AV tipe papulopustular dan AV tipe komedonal.…”
unclassified